A Critical Analysis of Mughal Culture in the Writings of Foreign Travelers - Anshuman Suman (HISTORICAL: Journal of History and Social Sciences, 2025)
This study critically analyzed the writings of foreign travelers to the Mughal Empire to understand how the empire’s culture, society, and administration were perceived and represented. Significant research gaps were identified, including the predominant focus on elite European travelers, underrepresentation of lesser-known observers, limited cross-referencing with indigenous sources, and insufficient attention to cultural dimensions such as art, architecture, literature, music, courtly rituals, and religious practices. The primary objective was to reconstruct a nuanced understanding of Mughal cultural life by examining foreign narratives alongside Persian chronicles, administrative manuals, and vernacular texts, thereby highlighting biases, accuracies, and omissions in these accounts. Through this process, the study provided a critical assessment of Mughal courtly etiquette, festivals, literary traditions, urban and architectural aesthetics, and ceremonial practices, revealing both the sophistication of the empire and the interpretive frameworks of the travelers.